Determining Culex annulirostris larval densities and control efforts across a coastal wetland, Northern Territory, Australia. Issue 2 (17th November 2016) - Kurucz, N.; Jacups, S.; Carter, J.M.
ABSTRACT: The Darwin coastal wetlands provide suitable breeding conditions for Culex annulirostris, which is abundant between December and August each year. This species is the principal vector for arboviruses, including Ross River virus and Murray Valley encephalitis, and is an appreciable pest species. Aerial control is conducted when routine larval surveys for this species predict high numbers of emergent adults. We sought to determine the most productive vegetation categories and seasonal aspects associated with Cx. annulirostris breeding and control operations in these wetlands. By applying a generalized linear model to compare larval densities and aerial control efforts for each vegetation category, we found that Schoenoplectus reeds were the most productive vegetation type in May and June and were associated with the greatest amount of control required. Other vegetation categories associated with tidal mangroves and lower topographic elevation were also productive during these months for extended periods, while rain‐affected reticulate areas and grassland floodplains were most productive in January and April. In addition, areas associated with nutrient rich organic matter appeared to initiate Cx. annulirostris breeding and were highly productive seasonally. This study has highlighted the vegetation categories most significantly associated with Cx. annulirostris breeding in a Darwin wetland. This knowledge can be applied to current control efforts to improve aerial control efficiency for this species and could be applicable in other areas of northern Australia.